The Rise of Online Gambling and Its Securitization Efforts in Indonesia Post COVID-19 - Farisin, Mokhamad Saiful (Global and Policy Journal of International Relations, 2025)
Online gambling activities in Indonesia have seen a significant increase in recent years, particularly during the Covid-19 pandemic. One of the factors contributing to this rise is boredom due to social distancing measures implemented to minimize the spread of the virus. This rapid increase has turned online gambling into a serious threat for Indonesia, necessitating immediate action to address the issue. This research aims to examine the securitization stages undertaken by the Indonesian government to tackle this threat, using the securitization theory of The Copenhagen School. Through descriptive research methods and a literature review, it was found that the online gambling issue has been successfully securitized by the Indonesian government through three stages: speech act, acceptance by the audience, and emergency measures. The author also discovered that during the acceptance by the audience stage, the response received was substantial and varied, ranging from individuals to institutions, indicating that the issue has gained attention from the target audience of this securitization effort.